RETRACTED: Water Tower Conservation and Sriwijaya University Law Efficiency Based on Indonesian Green Building Certification - Indriyati, Citra; Izzah, Saniatul (Journal of Applied Science, Engineering, Technology, and Education, 2022)
This article has been retracted: please see ASCI Policy on Article Withdrawal (https://ascijournal.eu/index.php/asci/plagiarism). This paper is retracted at the request of the Authors.